PENAMBAHAN SARI JAHE GAJAH PADA UJI ORGANOLEPTIK PERMEN KARAMEL SUSU - Luklu Ul Ummah; Agustina Widyasworo; Resti Yuliana Rahmawati (AVES: Jurnal Ilmu Peternakan, 2021)
The purpose of this study was to determine the effect of the addition of ginger juice on the organoleptic test of milk caramel candy. This study used a completely randomized design method (RAL) whith 4 treatmens and 3 replications, where each tretmen P0 (control), P1 (50ml), P2 (100ml), and P3 (150ml). then analyzed using analysis of variance (ANOVA) and Duncan test. The result of this study indicate that the highest valui for color P2 is (chocolate), aroma is P3 (sweet), texture is P3 (soft), teste is P0 (typical of milk candy). The conclution of this study is that the addition of ginger juice has a significant effect on color, aroma, texture, and teste. Suggestions from this study are that it can be used as a reference material and a laboratory test the content of milk caramel candy